Java-Sunda Students’ Appreciation on The Learning of Rejang Language as A Local Subject in Elementary Schools, North Bengkulu - Asmahasanah, Salati; Zulela; Marini, Arita; Sumantri, Mohamad Syarif (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
This study is about the appreciation of students of SD Negeri 158 Air Baus, a transmigration area which is dominated by Javanese and Sundanese people, towards learning Bahasa Rejang as the original language and oldest ethnic group in Bengkulu province. In North Bengkulu district, Rejang language is a compulsory subject as an effort of the government to preserve the culture and language. Considering the facts that Rejang is in the category of nearly went extinct language and rarely used by today's youth. This research uses qualitative ethnographic methods. The findings of this study are 1) Students from Javanese-Sundanese ethnic group, on average, find that Rejang language is difficult to learn, especially when learning to pronounce and understand it, 2) Students learn the local subject of Rejang language through reading, writing, singing, imitating the teacher, listening and practicing independently, 3) The materials studied are KaGaNga script, counting, reading stories, types of animals, types of plants, types of objects and others, 4) Students also have a problem learning Rejang script because the letter symbols used are very different with daily grammar.